Penerapan Model Project-Based Learning Pada Mata Pelajaran Instalasi Tenaga Listrik - Fattah, Raihan Abdul; Islami, Syaiful (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to determine the application of the Project-based learning model in the Electrical Power Installation subject at SMK Negeri 2 Payakumbuh. This research uses experimental research methods. The research design used was a pre-experimental one group pretest posttest design. This design involves one group being given a pretest (O1), given treatment (X) and given a posttest (O2). The subjects of this research were all students of class XI TITL 2 SMKN 2 Payakumbuh for the 2023/2024 academic year. The first measurement is carried out before the subject is given treatment and the second measurement is carried out after the subject is given treatment. The research results show that the application of the Project-based learning model in the Electrical Power Installation subject class XI TITL 2 SMK Negeri 2 Payakumbuh can improve student learning outcomes. These results can be seen from the knowledge domain, namely the pretest and posttest results which were analyzed using the N-Gain Score formula into the medium category and using completeness the learning results increased from the medium category to very high. By obtaining this data, it can be concluded that by implementing the Project-based learning model, the learning outcomes of class XI TITL 2 students have greatly increased in the Electrical Power Installation subject.